North Korea and the Politics of Visual Representation - David Shim; Dirk Nabers (German Institute of Global and Area Studies (GIGA), 2011)
Within international discourses on security, North Korea is often associated with risk and danger, emanating paradoxically from what can be called its strengths - particularly military strength, as embodied by its missile and nuclear programs - and its weaknesses - such as its ever-present political, economic, and food crises - which are considered to be imminent threats to international peace and stability. We argue that images play an important role in these representations, and suggest that one should take into account the role of visual imagery in the way particular issues, actions, and events related to North Korea are approached and understood. Reflecting on the politics of visual representation means to examine the functions and effects of images, that is what they do and how they are put to work by allowing only particular kinds of seeing. After addressing theoretical and methodological questions, we discuss individual (and serial) photographs depicting what we think are typical examples of how North Korea is portrayed in the Western media and imagined in international politics.
Keywords: 300; visual representation; synecdoche; identity; North Korea; Nordkorea; Öffentliche Meinung; Industriestaaten